Rela????o entre valores pessoais e faturamentos individuais da for??a de vendas em uma empresa cosm??tica de venda direta - Lucchi, Melissa (2015)
Since 1985, personal characteristics are recognizes as determinants of salesperson performance, but the majority of international studies that investigate the relation between sales personal values and objective performance don???t include the sales force (vendors and sales managers) in the samples. Relating to Personal Selling firms, researches show that the personal value ???effort??? is related to high performance. Relational values, highly present in social and informal sales contexts as the Personal Selling, are neglected, not being related to positive individual performances. Adopting the Organizational Culture as theoretical framework, this study investigates the relation between the sales force??s (Sales Executives - EVs and Beauty Consultants - CBs) personal values of the Direct Selling firm Pierre Alexander Cosmetics (PA) and individual revenues obtained by these professionals. This was accomplished by the use of direct observations and the C-VAT Methodology (Culture and Values Analysis Tool) and the PVP questionnaire (Personal Values Profile), that 415 PA members answered between 2012 and 2014. The answers were analyzed by the Cluster Analysis Technique and show a Company composed by women that are more than 40 years of age and work at PA for more than 15 years. Their values are strong in Work and effort is the main one, united to work quality and to relational dimensions as loyalty, empathy and sociability. In a second moment, the relation between personal values and individual revenues of the sales force in the year 2013 was interpreted by frequency distribution methods. This research concluded that personal values related to Work are fundamental to obtain high individual performance from the CBs (sellers). On the other hand, relational values are most important to motivate the EV???s (coordinator) team of sellers. Differing from what affirms the literature on the area, personal values that help in sales differ from personal values that base the motivation of others to sales (EVs objective).